Behaviour on public transportation - the study on priority seats in Singapore. - Lim, Shan Shan. (2013)
This research mainly focuses on how commuters negotiate their spaces on public transportation and the impact of social sanctions on behaviors based on the sociology of mobility. Mobility studies have been seen as part of everyday life that is taken for granted. The travel journey on public transportation should be constructed as a meaningful platform for social interactions. To provide a deeper understanding of social interactions amongst social actors on public transportation in Singapore, priority seats have been used as a point of contention to determine if social sanctions play a role in shaping social behaviors. Using Gidden’s structuration theory, the action of giving up priority seats highlights the duality of structure and agency, in which determines how social sanctions affect people’s agency in deciding their seats. This study also serves to justify how social structure is constructed in everyday interactions through social sanctions imposed on the occupancy of priority seats in Singapore.